The development of creativity in adolescents: a qualitative study of how and where creativity develops - Morrell, Michelle A., author; Coke, Pamela, advisor; O'Donnell-Allen, Cindy, committee member; Frederiksen, Heidi, committee member (Colorado State University. Libraries, 2015)
To best prepare current K-12 students for what will likely be an unfamiliar and changing future, teachers and educational professionals today consider "21st century skills" among the tools students will need, and chief among those skills is creativity. An understanding of how and where creativity happens, from the perspective of children and adolescents, could provide valuable information to educators who seek to prepare students for the work-force of tomorrow. This study seeks to answer the following questions through gaining the perspectives of a female and a male at the eighth grade level and their English language arts teacher: 1. What is creativity? 2. How does creativity happen? 3. Where does creativity happen? From the perspective of the student study participants whom I interviewed, creativity is an individualistic expression of one’s thoughts generated in an individual’s mind and then expressed in a visual or concrete media. Creativity is a process and a result of years of involvement, is aided by internal or external motivators as well as the presence of examples and feels good when it happens. Creativity does not happen if strict rules or constraints are imposed. For theses interviewees, creativity can happen almost anywhere, and is aided by quite, alone time when the creator has time to process his/her thoughts. Allowing students the time, space, and resources they each require to encourage their creativity process will not only enable creativity to happen but will make the process more accessible and familiar, developing creative response as a habit, not an exception.